2000
DOI: 10.1097/00006842-200009000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Differences Between Veterans With and Without Gulf War Unexplained Symptoms

Abstract: Our results revealed that Gulf War veterans who report symptoms associated with that conflict differed on multiple psychological measures in the direction of increased distress and performed more poorly on neurobehavioral measures when compared with control subjects who did not report symptoms. This suggests that psychological differences have a prominent role in investigation of possible explanations of Gulf War symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 39 publications
1
27
1
Order By: Relevance
“…Thus, these data suggest the possibility of sensorimotor deficits in the veterans of PGW, who may have been exposed to PB or sarin. These results are consistent with the epidemiological studies reported by Knoke et al (2000) and Storzbach et al (2000).…”
Section: Discussionsupporting
confidence: 94%
“…Thus, these data suggest the possibility of sensorimotor deficits in the veterans of PGW, who may have been exposed to PB or sarin. These results are consistent with the epidemiological studies reported by Knoke et al (2000) and Storzbach et al (2000).…”
Section: Discussionsupporting
confidence: 94%
“…The lack of effective inhibition as demonstrated in both behavioral performance and in electrophysiological responses may be able to account for multiple other symptomatic complaints. For example, a lack of effective inhibition can represent a plausible etiology for the deficits in executive function [3,8,14,15,58,59], attention [8,[59][60][61][62], and abstraction/problem solving [60,63]. Because it can account for such a wide array of symptoms, impairment in inhibition is compatible with the variety of complaints reported by GW veterans, although they may not specifically report 'a lack of inhibition.'…”
Section: Discussionmentioning
confidence: 99%
“…The test battery consisted of eight tests of the ATSDR Adult Environmental Neurobehavioral Test Battery (ATSDR, 1995) and six tests of the Oregon Health and Sciences University's Behavioral Assessment and Research System (BARS). A 36-item questionnaire was used to assess possible psychological or medical problems (Storzbach et al, 2000). The Spanish version protocol was pilot tested at the Oregon Health and Sciences University's CROET laboratory (Portland, OR).…”
Section: Neurobehavioral Testsmentioning
confidence: 99%